DANDY-WALKER VARIANT (DWV) IN 70 YEARS OLD WOMAN WITH DISEQUILIBRIUM AND CENTRAL VERTIGO : A CASE REPORT - Ria Damayanti; Muhammad Welly Dafif; Shahdevi Nandar Kurniawan; Badrul Munir; Zamroni Afif (Journal of Pain, Headache and Vertigo, 2020)
Dandy Walker Syndrome (DWS) and its Variants (DWV) is a congenital disorder that has prevalence of 1 in 25,000 to 30,000 births with the highest incidence occurs at age <1 year. However, patients may be diagnosed with DWS/DWV for the first time in adolescence and even old age. We reported the 70-year-old woman with a chief complaint of central type vertigo accompanied by disequilbrium. From history taking we obtained disequilibrium with gradual onset started in nine months and become settled since the last 6 months before she came to the neurology clinic. The patient also complained vertigo that have emerged since the last 3 month. A history of head trauma, stroke, dementia was denied. Physical examinaton show central nystagmus while other cranial nerve within normal range. Motor, sensory and autonomic status within normal range. Romberg test, tandem walking, disdiadokokinesia, and dismetria examination shows abnormal respons. MMSE results for patients within normal range (score:26). Head MRI shows Dandy Walker Variant in the accompanied by cerebral atrophy and degeneration serebelli Fazekas grade I. Patients receive symptomatic therapy betahistine mesylate 3x6 mg if necessary. Surgery management is not indicated because there is no sign of hydrocephalus or signs of increased intracranial pressure.